Параметри поля у фокальній області круглої апертури, що сфокусована у зону Френеля - Горелов, О. Ю. (ХНУРЕ, 2025)
In this paper, analytical expressions are obtained for calculating the main parameters characterizing the longitudinal distribution of the circular focused aperture field intensity with a relatively large diameter (2𝑅 𝜆 ⁄ ≥10): the dis placement of the intensity maximum relative to the focal point, focusing gain and depth of focus. Cases of uniform and decreasing amplitude distributions of the excitation field are considered. The found approximate relations make it possible to determine the values of the above parameters for any values of the longitudinal coordinate of the focal point, lying both in the Fresnel zone and in the far zone. Comparison with numerical calculations
Keywords: зона Френеля; кругла апертура